British Political Facts - Butler, D. author. aut Link
XVII, 625 p.
Keywords: The 10th edition of a library classic, British Political Facts records the who, the what and when of British political life from 1900 to the present day. Thoroughly researched and updated, this reliable and unique work is a treasure trove of information for scholars and politicos alike.